Plasticity of spatial hearing: Behavioural effects of cortical inactivation - Nodal, F; Bajo, V; King, A (2012)
The contribution of auditory cortex to spatial information processing was explored behaviourally in adult ferrets by reversibly deactivating different cortical areas by subdural placement of a polymer that released the GABA agonist muscimol over a period of weeks. The spatial extent and time course of cortical inactivation were determined electrophysiologically. Muscimol-Elvax was placed bilaterally over the anterior (AEG), middle (MEG) or posterior ectosylvian gyrus (PEG), so that different regions of the auditory cortex could be deactivated in different cases. Sound localization accuracy in the horizontal plane was assessed by measuring both the initial head orienting and approach-to-target responses made by the animals. Head orienting behaviour was unaffected by silencing any region of the auditory cortex, whereas the accuracy of approach-to-target responses to brief sounds (40 ms noise bursts) was reduced by muscimol-Elvax but not by drug-free implants. Modest but significant localization impairments were observed after deactivating the MEG, AEG or PEG, although the largest deficits were produced in animals in which the MEG, where the primary auditory fields are located, was silenced. We also examined experience-induced spatial plasticity by reversibly plugging one ear. In control animals, localization accuracy for both approach-to-target and head orienting responses was initially impaired by monaural occlusion, but recovered with training over the next few days. Deactivating any part of the auditory cortex resulted in less complete recovery than in controls, with the largest deficits observed after silencing the higher-level cortical areas in the AEG and PEG. Although suggesting that each region of auditory cortex contributes to spatial learning, differences in the localization deficits and degree of adaptation between groups imply a regional specialization in the processing of spatial information across the auditory cortex. © 2012 The Authors. The Journal of Physiology © 2012 The Physiological Society.